PENTINGNYA MEMILIH MAKANAN BERLABEL HALAL: EDUKASI BAGI SISWA-SISWI SEKOLAH DASAR - Utami, Setyo; Ratnasari, Khurin In; Munawir, Achmad; Irfani, Amaria; Asy’ari, Yuszri Thoha (Pandalungan: Jurnal Pengabdian kepada Masyarakat, 2025)
Halal literacy among elementary school students remains low, particularly in their ability to recognize and understand the meaning of halal logos on food and beverage packaging. This condition may influence children’s consumption patterns from an early age, given the high exposure to snacks and processed food products in the school environment. Therefore, systematic, contextual, and participatory halal education is needed. This community service program aimed to improve elementary school students’ understanding and awareness of the importance of choosing halal-labeled food through a Community-Based Participatory Research (CBPR) approach. The program was implemented at SDN Wonorejo 1, Kencong District, Jember Regency, and consisted of initial observation, pre-test, interactive socialization on halal logos and fatwas issued by the Indonesian Council of Ulama (MUI), label-reading practice, and evaluation through post-test and discussion. The results showed a significant improvement in students’ knowledge and attitudes toward the importance of halal food consumption, as evidenced by paired sample t-test analysis. Interactive halal education delivered at an early age was proven effective in shaping students’ awareness and positive habits in food selection. This program has strong potential to be replicated in other schools as part of efforts to strengthen halal literacy and character education.